2021
DOI: 10.3390/molecules26071968
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, In Vitro Bioaccessibility and Antioxidant Activity of Polyphenolic Compounds from Nutraceutical Fennel Waste Extract

Abstract: Fennel (Foeniculum vulgare Mill.) waste contains a broad range of bioactive molecules, including polyphenols, which have poor bioaccessibility during gastrointestinal digestion. This work aimed to investigate the bioaccessibility of total phenolic compounds and the antioxidant capacity during simulated gastrointestinal digestion using two nutraceutical formulations based on non-acid-resistant (NAR) and acid-resistant (AR) capsules containing aqueous-based extracts from fennel waste. Moreover, to obtain a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…Moreover, when compared to NARC samples, the pea pods water-based extracts contained in ARC formulation highlighted a significantly higher antioxidant activity and TPC value in both the duodenum and colonic stages. These findings are in agreement with a previous study that reports that water-based extracts from fennel waste in the ARC formulation showed high polyphenol bioaccessibility in the colonic stage after simulated GI digestion [ 29 ]. Moreover, Izzo et al [ 58 ] also demonstrated that red cabbage extract contained in ARC formulations showed higher colon bioaccessibility than the not-encapsulated extract.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, when compared to NARC samples, the pea pods water-based extracts contained in ARC formulation highlighted a significantly higher antioxidant activity and TPC value in both the duodenum and colonic stages. These findings are in agreement with a previous study that reports that water-based extracts from fennel waste in the ARC formulation showed high polyphenol bioaccessibility in the colonic stage after simulated GI digestion [ 29 ]. Moreover, Izzo et al [ 58 ] also demonstrated that red cabbage extract contained in ARC formulations showed higher colon bioaccessibility than the not-encapsulated extract.…”
Section: Discussionsupporting
confidence: 93%
“…Water-based extract from a pea pod was obtained following a procedure previously described [ 29 ]. In short, 10 g of pulverized samples were added to 200 mL of hot water (80 °C).…”
Section: Methodsmentioning
confidence: 99%
“…HRMS based on time-of-flight (TOF) and Orbitrap analyzers is the technique of choice for a comprehensive characterization of plant-based extracts due to the higher-resolution capabilities and the accurate mass measurements (with errors below 2 ppm depending on the instrument). In these cases, hybrid configurations combining quadrupole and ion-trap analyzers coupled with HRMS instruments such as Q-TOF [95][96][97][98][99][100], IT-TOF [101], and Q-Orbitrap [102,103] were preferred to take advantage of the high sensitivity of these platforms under full-scan acquisition mode. Furthermore, fragmentations can be employed for identification purposes, especially when profiling strategies are applied.…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…Several polyphenols such as 3-caffeoylquinic acid, methyl 4-caffeoylquinate, kaempferol-acetyl-glycoside, quercetin 3-rutinoside, quercetin-acetylglycoside, kaempferol 3-O-glucoside, and quercetin 3-O-glucoside were identified. In another work, a Q-Orbitrap HRMS instrument was used to assess a comprehensive investigation of the polyphenolic constituents of fennel waste extract, showing that chlorogenic acids were the most abundant compounds [102]. Some applications based on MS instruments with an even higher resolution than an Orbitrap analyzer, such as Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS), have also been described in the literature.…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…Among mono-isomers, 5-CQA is the major extracted phenolic compound (3.7 and 8.9 mg/g dw in outer bracts and stems, respectively) followed by 3-CQA in stem extract and 1-CQA in bract extract. Quite high amounts of CGAs were detected also in blueberry leaves (47.271 ± 0.1803–51.631 ± 0.4703 mg/g dw) [ 31 ], almond skin (15.99 ± 0.19 mg/g) [ 32 ], carrot pomace (17.79 ± 0.30 mg/g) [ 33 ], pomegranate peel (307.26 mg/L) [ 34 ], walnut leaves (8.6 ± 0.98–10.7 ± 1.45 mg of 3CQA/g dw) [ 35 ], fennel bulbs waste (1.949 ± 0.142 mg of 4CQA/g dw and 0.490 ± 0.035 mg of 3,4-di-CQA/g dw) [ 36 ]. CGAs content in tomato skin by-products, depending on the applied extraction method, amounts to 6–62 mg/kg according to Tranfić Bakić et al [ 37 ], 4.05 ± 0.07 mg/kg dw according to Pellicanò et al [ 38 ] and 304.45–454.34 mg/100 g based on the study by Ninčevic Grassino et al [ 39 ].…”
Section: Chlorogenic Acids In Agri-food Wastesmentioning
confidence: 99%